Functional and regulatory conservation of the soybean ER stress-induced DCD/NRP-mediated cell death signaling in plants. Issue 1 (December 2016) - Reis, Pedro; Carpinetti, Paola; Freitas, Paula; Santos, Eulálio; Camargos, Luiz; Oliveira, Igor; Silva, José; Carvalho, Humberto; Dal-Bianco, Maximiller; Soares-Ramos, Juliana; Fontes, Elizabeth
Abstract Background The developmental and cell death domain (DCD)-containing asparagine-rich proteins (NRPs) were first identified in soybean (Glycine max ) as transducers of a cell death signal derived from prolonged endoplasmic reticulum (ER) stress, osmotic stress, drought or developmentally-programmed leaf senescence via the GmNAC81/GmNAC30/GmVPE signaling module. In spite of the relevance of the DCD/NRP-mediated signaling as a versatile adaptive response to multiple stresses, mechanistic knowledge of the pathway is lacking and the extent to which this pathway may operate in the plant kingdom has not been investigated. Results Here, we demonstrated that the DCD/NRP-mediated signaling also propagates a stress-induced cell death signal in other plant species with features of a programmed cell death (PCD) response.In silico analysis revealed that several plant genomes harbor conserved sequences of the pathway components, which share functional analogy with their soybean counterparts. We showed that GmNRPs, GmNAC81 andVPE orthologs from Arabidopsis, designated asAtNRP -1, AtNRP -2, ANAC036 andgVPE, respectively, induced cell death when transiently expressedin N. benthamiana leaves. In addition, loss ofAtNRP1 andAtNRP2 function attenuated ER stress-induced cell death in Arabidopsis, which was in marked contrast with the enhanced cell death phenotype displayed by overexpressing lines as compared to Col-0. Furthermore, atnrp-1 knockout mutants displayed enhanced sensitivity to PEG-induced osmotic stress, a phenotype that could be complemented with ectopic expression of eitherGmNRP -A orGmNRP -B . In addition, AtNRPs, ANAC036 andgVPE were induced by osmotic and ER stress to an extent that was modulated by the ER-resident molecular chaperone binding protein (BiP) similarly as in soybean. Finally, as putative downstream components of the NRP-mediated cell death signaling, the stress induction ofAtNRP2, ANAC036 andgVPE was dependent on theAtNRP1 function. BiP overexpression also conferred tolerance to water stress in Arabidopsis, most likely due to modulation of the drought-induced NRP-mediated cell death response. Conclusion Our results indicated that the NRP-mediated cell death signaling operates in the plant kingdom with conserved regulatory mechanisms and hence may be target for engineering stress tolerance and adaptation in crops.